A novel efficient RhB absorbent of Mo2N/MoO2 composite nanofibers for wastewater treatment. Issue 5 (12th January 2020) - Cheng, Jing; Xing, Yan; Wang, Ziyuan; Zhao, Xiaohui; Zhong, XiQiang; Pan, Wei
Abstract: Mo2 N/MoO2 composite nanofibers have been prepared via an electrospinning and controlled nitridation process. The composite nanofibers exhibit a highly efficient Rhodamine B (RhB) absorption behavior with a rate constant of 0.153 g min −1  mg −1, which is about 20 times of the commercial‐activated carbon material. Furthermore, the nanofibers show stable absorption activity after recycled by an environmental friendly procedure for four times. The excellent absorption performance of Mo2 N/MoO2 composite nanofibers demonstrates a promising application of Mo2 N‐related materials as an absorbent for wastewater treatment.